DETERMINANTES DE LA CONTAMINACIÓN ATMOSFÉRICA EN AMÉRICA LATINA Y EL CARIBE: UN ANÁLISIS DE DATOS DE PANEL, PERIODO 1990 – 2016 - Caraguay Gómez, Leidy Carolina (2019)
Air pollution is a problem that has increased notably as a result of the various anthropogenic activities carried out by man for his development, representing a great risk for humanity, ecosystem and negatively influencing the economy. In this context, this research has the general objective to examine the relationship between atmospheric pollution and he’s determinants in Latin America and the Caribbean in the period 1990-2016, through a descriptive and econometric study of panel data. The independent variables are economic growth, fossil energy use and total population; the dependent variable is the total of greenhouse gas emissions (GHG) as a measure of air pollution. We used panel data models using the cointegration test of Pedroni (1999) and Westerlund (2007) in order to identify the equilibrium relationship in the short and long term, respectively, and Granger's model (1988), based on the test proposed by Dumitrescu and Hurlin (2012) to verify the causality between the variables. The results revealed that economic growth, the use of fossil energy and the total population have a significant influence on air pollution. For the application of public policies, the level of development of each economy in the region must be considered in order to reduce emissions and achieve sustainable economic growth.